CRISPR/Cas precision: do we need to worry about off-targeting in plants? - Hahn, Florian (Plant Cell Rep, 2018)
The CRISPR/Cas technology has recently become the tool of choice for targeted genome modification in plants and beyond. Although CRSIPR/Cas offers a rapid and facile way of introducing changes at genomic loci of interest, its application is associated with off-targeting, i.e. introduction of unintended mutations at off-target sites within the genome, which has been reported frequently in the mammalian field. Here we summarise the current knowledge on the precision of CRISPR/Cas in plant systems and provide a summary of state-of the-art strategies for avoiding off-target mutations, as well as unintended on-target changes, in plants. These include using natural (e.g. Cas12a) or engineered (e.g. SpCas9-HF) CRISPR/Cas nucleases characterised by higher precision, as compared to the commonly used wild type SpCas9. In addition, we discuss the usage of CRISPR/Cas nucleases in the form of ribonucleoproteins (RNPs) as an option for reducing off-targeting in plants. Finally, we conclude that the most important factor for reducing CRISPR/Cas off-targeting remains careful selection of target sequences, for which we provide an overview of available online software tools and experimental guidance.